"Model of Technical Innovation: A Study of E-banking Adoption” - Anubha Srivastava, Prof A.K. Saxena, Dr. Suman Yadav, Dr. K.R. Chaturvedi (International Journal of Advanced Science and Technology, 2020)
The banks operating in India are spending tremendous amount of cash on technological frameworks to acquire various set of preferences, e.g. cutting expenses and enhancing the nature of services through technological innovation (E-banking); because it is well accepted phenomena that technological innovation reduces time consumption, error propensity and cost of the services. If people are not willing to acknowledge and completely use E-banking services, it won’t convey full advantages to the Companies. To understand people’s psyches behaviour towards tolerating or dismissing technology has turned out to be a standout amongst the most difficult issues in technological frameworks inquires about. This paper aims to develop a technology adoption model from the customer’s perspective and the study lights on the existence of significant association among the variables considered for the study.